Sistem Informasi Manajemen Magang dengan Metode System Integration di Biro Kesejahteraan Rakyat Setdaprovsu - Muhammad Rizki Fadillah; Samsudin Samsudin; Vidya Ramadhani (Jurnal Informatika, 2024)
Efficient internship recruitment management is one of the important elements in supporting human resource management, but the implementation of services at the Bureau of People's Welfare of the North Sumatra Provincial Secretariat is still constrained by manual processes, lack of system integration, and low efficiency. This study aims to improve the quality of internship recruitment management through the application of the process optimization method using the Waterfall Model approach. This method involves the stages of needs analysis, system design, implementation, testing with the black-box method, and maintenance of PHP and MySQL-based systems. The results of the study showed that the information system developed succeeded in increasing work efficiency, reducing errors in data recording, accelerating the selection process, and clarifying access to information for users, both administrators and interns. This system also proved to be responsive to user needs with appropriate feature validation. The conclusion of this study is that the process optimization method is able to significantly improve the performance of internship recruitment services. The researcher suggests that employee training be carried out continuously to ensure mastery of the system, as well as improving technology infrastructure so that the system can adapt to future needs and support the sustainability of services.